PELATIHAN PEMASARAN DARING BAGI KELOMPOK USAHA PENGOLAHAN IKAN MINA SEKAR DI DESA TAMBAK OSO - Muchammad Tamyiz; Waluyo Prasetyo; Fuad Achmadi (Universitas Nahdlatul Ulama Sidoarjo, 2019)
The availability of coastal natural resources provides a great opportunity for residents of Tambak Oso village. This condition makes the residents of Tambak Oso village create a business group